Signal propagation in long wire chambers - Bock, Peter; Heintze, Joachim; Lennert, Peter (Journal of Instrumentation, 2012)
The propagation of signals in long proportional counters or multi-wire tracking chambers is simulated, using numerical solutions of the multi-wire telegraph equations. The results are compared to experimental data, recorded with a proportional counter and a multi-wire test chamber. The signal shape, the charge division ratio and, in the case of the drift chamber, also the cross talk between the wires, are well reproduced. Similar shapes for signals and their cross talk can be obtained with a properly chosen electrical termination. It is shown how data from a multi-wire chamber can then be corrected for cross talk. The effects limiting the precision of position measurements along the wires with the charge division method are discussed. The simulation was applied to the reconstruction of tracks measured with the OPAL JET chamber.
Gesehen am 11.10.2018